Preparation and application of alkali-loaded polymer composite membrane

By preparing alkali-loaded polymer composite membranes, using their mesh porous structure to efficiently remove trace acid from organic solvents, the shortcomings of alkali washing and distillation in the prior art are solved, and efficient, economical and environmentally friendly deacidification is achieved Effect.

CN119215694APending Publication Date: 2024-12-31LISHUI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411543058.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the prior art, when removing trace organic acids from organic solvents, it is difficult to determine the amount of alkali added by alkali washing method, which may lead to excessive or hydrolysis. The distillation method is not suitable for volatile solvents and has high energy consumption, making it difficult to efficiently and economically Deacid.

Method used

A polymer composite membrane with alkali-supported alkali is prepared, and a polymer membrane with a mesh porous structure is formed through the preparation of crosslinking agent, polymerization reaction and the loading of alkaloids, which is used to efficiently remove trace acids in organic solvents.

Benefits of technology

It has achieved efficient removal of trace acids from organic solvents, has good thermal stability and low moisture absorption properties, is suitable for industrial production, and has recycling and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215694A_ABST
    Figure CN119215694A_ABST
Patent Text Reader

Abstract

The invention provides preparation and application of an alkali-loaded polymer composite membrane. The preparation method of the alkali-loaded polymer composite membrane comprises the following steps: (1) preparing a cross-linking agent; (2) preparing a polymer composite membrane; and (3) preparing the alkali-loaded polymer composite membrane. The polymer composite membrane prepared by the invention has good thermal stability, can efficiently remove trace organic acid in an organic solvent after successfully loading green and environment-friendly alkaloid, has certain recyclability, and has wide application prospects in the field of deacidification of acid-containing organic solvents.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials and relates to the preparation and application of a polymer composite membrane loaded with alkali. Background Art

[0002] In the process of production, storage and use, there may be operational errors and improper storage of organic solvents, which may lead to the incorporation of small amounts or trace amounts of organic acids, thereby reducing the purity of organic solvents and causing certain adverse effects on the subsequent use of organic solvents. Therefore, it is necessary to deacidify the acid-containing organic solvents.

[0003] At present, the common deacidification methods of organic solvents in industry include alkali washing method, distillation method, etc. Among them, alkali washing method is a classic deacidification process and is relatively mature. Generally, liquid alkali (such as sodium hydroxide, potassium hydroxide, etc.) is used to neutralize the impurity acid in the organic solvent. However, for the removal of trace acids, the dosage of liquid alkali is difficult to determine, and too much will be added if you are not careful. In addition, the liquid alkali contains water, which may cause some organic solvents to hydrolyze and affect the overall quality of the organic solvent. The distillation method uses high-temperature heating to deacidify, but this method is not suitable for volatile organic solvents. High temperature may cause the organic solvent and organic acid to produce azeotropy, resulting in the loss of organic solvents. In addition, the high-temperature heating method will generate a lot of energy consumption, which is not economical for the deacidification of organic solvents containing trace acids. Therefore, the removal of small or trace organic acids in organic solvents is still a problem that needs to be solved urgently. Summary of the invention

[0004] In view of the above problems in the prior art, the technical problem to be solved by the present invention is to provide a method for preparing an alkali-loaded polymer composite membrane, with the aim of developing an alkali-loaded polymer membrane that can efficiently remove trace organic acids in organic solvents and is recyclable.

[0005] The technical solution of the present invention is as follows: A preparation and application of a polymer composite membrane loaded with alkali, wherein the preparation of the polymer composite membrane loaded with alkali specifically comprises the following steps: (1) Preparation of a cross-linking agent: In a beaker, tartaric acid and isocyanoethyl methacrylate were dissolved in tetrahydrofuran to obtain a solution A, and tartaric acid was dissolved in tetrahydrofuran to obtain a solution B. The two solutions were then mixed and stirred at 22-28°C for 22-25h. The tetrahydrofuran was removed by rotary evaporation at 60-70°C to obtain a cross-linking agent. (2) Preparation of polymer composite membrane: Add emulsifier OP-10, sodium dodecyl sulfate (SDS) and deionized water to a 250 mL four-necked flask (equipped with a condensation reflux device, a stirring device, and a constant pressure dropping funnel), stir at 400-600 rpm for 25-35 min, then slowly add butyl acrylate, methyl methacrylate and the crosslinking agent prepared in step (1) using a constant pressure dropping funnel, and continue stirring for 28-35 min. Then transfer the flask to an oil bath, add potassium persulfate solution and polytetrafluoroethylene powder under nitrogen, and polymerize at 78-85°C for 5.5-6.5 h. After the reaction is completed and cooled to 22-28°C, add ammonia water to adjust the pH to 7. Then the mixed solution was transferred to a beaker and a certain amount of ethanol was added, and after being placed in a ventilated place for 24 to 28 hours, the mixed solution was transferred to a polytetrafluoroethylene plate and dried in an oven at 58 to 65°C for 24 to 28 hours to obtain a polymer composite membrane; (3) Preparation of alkali-loaded polymer composite membrane: The polymer composite membrane prepared in step (2) is completely immersed in a saturated solution of alkaloids and allowed to stand for 22 to 26 hours, and then dried at 100 to 110° C. for 22 to 36 hours to finally obtain an alkali-loaded polymer composite membrane.

[0006] Preferably, in step (1), the mass ratio of tartaric acid, isocyanoethyl methacrylate and tetrahydrofuran in solution A is 1:(2-3):(9-11), and the mass ratio of tartaric acid and tetrahydrofuran in solution B is 1:(10-15).

[0007] Preferably, in step (2), the ratio of the mass (g) of sodium dodecyl sulfate (SDS), the mass (g) of emulsifier OP-10 and the volume (mL) of deionized water is 1: (1.5-1.8): (550-600).

[0008] Preferably, in step (2), the mass ratio of butyl acrylate, methyl methacrylate, and the cross-linking agent mixture prepared in step (1) is 1: (0.8-1.2): (0.5-1).

[0009] Preferably, in step (2), the mass ratio of sodium dodecyl sulfate (SDS) to butyl acrylate is 1:(30-35), and the mass ratio of butyl acrylate to polytetrafluoroethylene powder is 1:(4.2-4.5).

[0010] Preferably, in step (2), the ratio of the mass (g) of butyl acrylate to the volume (mL) of the potassium persulfate solution is 1:(1.5-1.8), wherein the concentration of the potassium persulfate solution is 10 g / L.

[0011] Preferably, in step (2), the volume ratio of ethanol to the original mixed solution in the beaker is 1:(0.5-0.8).

[0012] Preferably, the alkaloid in step (3) is berberine or matrine.

[0013] Preferably, the base-loaded polymer composite membrane prepared by the method as described above is used in deacidification of organic solvents.

[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. The polymer composite film prepared by the present invention has good thermal stability, which basically meets the requirements of deacidification treatment of acid-containing organic solvents in industrial production, and still has low moisture absorption performance after being loaded with alkaloids, which is conducive to stable storage in the later stage.

[0015] 2. The polymer composite membrane prepared by the present invention has a reticular porous structure, which is conducive to the stable loading of alkaloids by the internal microspheres, and can also increase the contact area between the acid-containing organic solvent and the membrane, thereby improving the deacidification effect of the membrane. In addition, the microspheres are loaded on the polymer membrane, which not only protects the microspheres, but also facilitates the recycling of the microspheres.

[0016] 3. The alkaloid-loaded polymer composite membrane prepared by the present invention has good deacidification performance and certain recyclability, and can efficiently remove trace organic acids in organic solvents in three cycles of deacidification treatment. In addition, the present invention uses alkaloids for deacidification, which is more environmentally friendly than inorganic alkali.

[0017] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention.

[0018] Instruction Manual Figure 1 is the Fourier infrared spectrum of the polymer composite film; Figure 2 The thermal stability test results of polymer composite membranes; Figure 3 is the SEM image of the polymer composite membrane; Figure 4 The microscopic morphologies of polymer composite membrane, Example 1 and Example 2, wherein (a) is polymer composite membrane, (b) is Example 1 and (c) is Example 2; Figure 5 is the liquid chromatogram of acetic acid standard; Figure 6 This is the liquid chromatogram of the organic solvent after the third deacidification treatment. DETAILED DESCRIPTION

[0019] The present invention is specifically described below by way of examples, which are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. It should be understood that after reading the contents of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

[0020] Example 1 The preparation steps of the alkali-loaded polymer composite membrane are as follows: (1) Preparation of cross-linking agent: In a beaker, 1.5 g of tartaric acid and 3.879 g of isocyanoethyl methacrylate were dissolved in 15 g of tetrahydrofuran to obtain solution A. Another 1.5 g of tartaric acid was dissolved in 20 g of tetrahydrofuran to obtain solution B. The two solutions were then mixed and stirred at 25°C for 23 h. The tetrahydrofuran was removed by rotary evaporation at 63°C to obtain a cross-linking agent.

[0021] (2) Preparation of polymer composite membrane: 0.3g emulsifier OP-10, 0.18g sodium dodecyl sulfate (SDS) and 100mL deionized water were added to a 250mL four-necked flask (equipped with a condensation reflux device, a stirring device, and a constant pressure dropping funnel). After stirring at 500rpm for 30min, 6g butyl acrylate, 6g methyl methacrylate and 3g of the cross-linking agent prepared in step (1) were slowly added dropwise using a constant pressure dropping funnel and continued to stir for 30min. The flask was then transferred to an oil bath, and 10mL potassium persulfate solution (10g / L) and 25.92g polytetrafluoroethylene powder were added under nitrogen, and the polymerization reaction was carried out at 80℃ for 6h. After the reaction was completed and cooled to 25℃, ammonia water was added to adjust the pH to 7. Then the mixed solution was transferred to a beaker and ethanol was added (the volume ratio of ethanol to the mixed solution was 1:0.6), and the mixture was placed in a ventilated place for 24 hours. The mixed solution was transferred to a polytetrafluoroethylene plate and dried in an oven at 60°C for 24 hours to obtain a polymer composite membrane.

[0022] (3) Preparation of alkali-loaded polymer composite membrane: The polymer composite membrane prepared in step (2) was completely immersed in a saturated solution of berberine and allowed to stand for 24 hours, and then dried at 100° C. for 36 hours to finally obtain an alkali-loaded polymer composite membrane.

[0023] Example 2 The preparation steps of the alkali-loaded polymer composite membrane are as follows: (1) Preparation of cross-linking agent: In a beaker, 1.5 g of tartaric acid and 3.879 g of isocyanoethyl methacrylate were dissolved in 15 g of tetrahydrofuran to obtain solution A. Another 1.5 g of tartaric acid was dissolved in 20 g of tetrahydrofuran to obtain solution B. The two solutions were then mixed and stirred at 22°C for 25 h. The tetrahydrofuran was removed by rotary evaporation at 60°C to obtain a cross-linking agent.

[0024] (2) Preparation of polymer composite membrane: 0.3g emulsifier OP-10, 0.18g sodium dodecyl sulfate (SDS) and 100mL deionized water were added to a 250mL four-necked flask (equipped with a condensation reflux device, a stirring device, and a constant pressure dropping funnel). After stirring at 400rpm for 35min, 6g butyl acrylate, 6g methyl methacrylate and 3g of the cross-linking agent prepared in step (1) were slowly added dropwise using a constant pressure dropping funnel and continued to stir for 35min. The flask was then transferred to an oil bath, and 10mL of potassium persulfate solution (10g / L) and 25.92g of polytetrafluoroethylene powder were added under nitrogen, and the polymerization reaction was carried out at 85℃ for 5.5h. After the reaction was completed and cooled to 22℃, ammonia water was added to adjust the pH to 7. Then the mixed solution was transferred to a beaker and ethanol was added (the volume ratio of ethanol to the mixed solution was 1:0.5), and the mixture was placed in a ventilated place for 26 hours. The mixed solution was transferred to a polytetrafluoroethylene plate and dried in an oven at 65°C for 26 hours to obtain a polymer composite membrane.

[0025] (3) Preparation of alkali-loaded polymer composite membrane: The polymer composite membrane prepared in step (2) was completely immersed in a saturated solution of matrine and allowed to stand for 26 hours, and then dried at 110° C. for 28 hours to finally obtain an alkali-loaded polymer composite.

[0026] Example 3 The preparation steps of the alkali-loaded polymer composite membrane are as follows: (1) Preparation of a cross-linking agent: In a beaker, 1.5 g of tartaric acid and 4.5 g of isocyanoethyl methacrylate were dissolved in 16.5 g of tetrahydrofuran to obtain solution A. Another 1.5 g of tartaric acid was dissolved in 22.5 g of tetrahydrofuran to obtain solution B. The two solutions were then mixed and stirred at 28°C for 22 h. The tetrahydrofuran was removed by rotary evaporation at 70°C to obtain a cross-linking agent.

[0027] (2) Preparation of polymer composite membrane: 0.324g of emulsifier OP-10, 0.18g of sodium dodecyl sulfate (SDS) and 108mL of deionized water were added to a 250mL four-necked flask (equipped with a condensation reflux device, a stirring device, and a constant pressure dropping funnel). After stirring at 600rpm for 25min, 6.3g of butyl acrylate, 7.56g of methyl methacrylate and 6.3g of the cross-linking agent prepared in step (1) were slowly added dropwise using a constant pressure dropping funnel and continued to stir for 28min. The flask was then transferred to an oil bath, and 11.34mL of potassium persulfate solution (10 g / L) and 28.35g of polytetrafluoroethylene powder were added under nitrogen, and the polymerization reaction was carried out at 78℃ for 6.5h. After the reaction was completed and cooled to 28℃, ammonia water was added to adjust the pH to 7. Then the mixed solution was transferred to a beaker and ethanol was added (the volume ratio of ethanol to the mixed solution was 1:0.8), and the mixture was placed in a ventilated place for 26 hours. The mixed solution was transferred to a polytetrafluoroethylene plate and dried in an oven at 58°C for 28 hours to obtain a polymer composite membrane.

[0028] (3) Preparation of alkali-loaded polymer composite membrane: The polymer composite membrane prepared in step (2) was completely immersed in a saturated solution of berberine and allowed to stand for 22 hours, and then dried at 105° C. for 22 hours to finally obtain an alkali-loaded polymer composite.

[0029] Comparative Example 1 The preparation steps of the alkali-loaded polymer composite membrane are as follows: (1) Preparation of cross-linking agent: same as in Example 1.

[0030] (2) Preparation of polymer composite membrane: same as Example 1.

[0031] (3) Preparation of alkali-loaded polymer composite membrane: The polymer composite membrane obtained in step (2) was completely immersed in a saturated solution of sodium hydroxide and allowed to stand for 24 hours, and then dried at 100° C. for 36 hours to finally obtain an alkali-loaded polymer composite.

[0032] Experimental methods The embodiments and comparative examples were tested, wherein the polymer chemical composition, thermal stability, surface morphology, alkali loading rate, water absorption, moisture absorption, and deacidification performance test methods are as follows: 1. Chemical composition test: The polymer composite film was studied by Fourier transform infrared spectroscopy (FTIR). The spectrum is 500-4000 cm -1 The wave number range is 4 cm -1 Record at a resolution of 1000 nm and scan 3 times.

[0033] Figure 1This is the Fourier infrared spectrum of the polymer composite film. As shown in the figure, the 1200 cm -1 and 1145 cm -1 The characteristic peaks are respectively attributed to the asymmetric stretching vibration of CF2 and the symmetric stretching vibration of CF2, indicating that the polytetrafluoroethylene powder exists in the polymer composite film. -1 The absorption peak at 1428 cm -1 The absorption peak is related to the bending vibration of the CH group. Therefore, the present invention successfully prepares the polymer composite film.

[0034] 2. Thermal stability test: The thermal stability of the samples was tested using thermogravimetric analysis (TGA), heating from 50°C to 900°C at a heating rate of 10°C / min.

[0035] Figure 2 The results of the thermal stability test of the polymer composite film can be seen from the figure. At the beginning, as the temperature rises, the polymer composite film sample shows a phenomenon of slow weight loss, and when the temperature reaches 357°C, the mass loss of the polymer film is only about 10%, which basically meets the treatment of acid-containing organic solvents in industrial production. After 357°C, the sample undergoes rapid thermal degradation, which is beneficial to the treatment of discarded polymer composite films to a certain extent. Therefore, the composite film prepared by the present invention has good thermal stability, which further ensures its safety during deacidification treatment.

[0036] 3. Surface morphology test: Use scanning electron microscopy to analyze the surface morphology of the composite. Prepare 1 cm*1 cm block samples for testing, and the magnification of the scanning electron microscope is selected from 4.0 k to 40.0 k. Use a ZS7050 stereo microscope to test the microscopic morphology of the sample.

[0037] Figure 3 It is the SEM picture of the polymer composite film. From Figure A, it can be seen that there are many different degrees of protrusions and depressions on the surface of the sample, and there is a rich porous structure. Focusing on one of the protrusion structures, after the precision continues to be amplified, it can be seen from Figure B that there is a complex network structure on its surface, and the appearance of this phenomenon is because polytetrafluoroethylene powder is added to the composite film. The porous network structure of the polymer composite film prepared by the present invention is conducive to the stable load of alkaloids, and the falling of alkali in the deacidification process can be avoided to a certain extent, and it is also conducive to increasing the contact area between the acid-containing organic solvent and the film, that is, the acid-containing organic solvent can enter the inside of the film through the porous, which is convenient for trace organic acids to fully combine with the alkaloids on the film, thereby improving the deacidification performance of the film.

[0038] Figure 4The microscopic morphology of the polymer composite membrane, Example 1, and Example 2. Figure (a) is the state of the polymer composite membrane without loading the alkaloid, showing that the membrane surface is relatively flat and has a certain degree of transparency. Many white spherical particles can be clearly seen on the membrane, indicating that the present invention successfully prepared a polymer membrane loaded with microspheres. Compared with the microspheres, the morphology of the composite membrane is conducive to rapid recovery after deacidification. At the same time, the membrane can play a certain protective role on the microspheres, avoiding the phenomenon of damage and falling of the microspheres during the deacidification process, thereby preventing the organic solvent from being "contaminated". Figures (b) and (c) are the microscopic morphologies of Example 1 and Example 2, respectively. Compared with the polymer composite membrane, the colors of the two have changed significantly. Example 1 is yellow as a whole, and Example 2 is light brown as a whole, indicating that the alkaloids have been successfully loaded on the polymer composite membrane. It can be further explained that during the alkali solution soaking process, the alkali solution can smoothly contact and adhere to the internal polymer microspheres through the mesh porous structure formed by polytetrafluoroethylene, and the microsphere particles can still be observed by careful observation. Therefore, the present invention successfully prepared a polymer membrane loaded with alkaloids.

[0039] 4. Alkali loading rate test: weigh the composite membrane before and after soaking in alkali solution, and record the mass respectively.

[0040] Table 1 shows the test results of the alkali loading rate of the polymer composite membrane. It can be seen from the table that the alkali loading rates of Example 1 and Example 2 are significantly higher than those of Comparative Example 1, wherein the alkali loading rate of Example 1 is more than 4 times that of Comparative Example 1, and that of Example 2 is more than 3 times that of Comparative Example 1, indicating that the loading efficiency of the polymer composite membrane prepared by the present invention for alkaloids (berberine, matrine) is significantly higher than that of sodium hydroxide. Therefore, the loading effect of the polymer composite membrane prepared by the present invention for alkaloids is better than that of ordinary inorganic bases.

[0041] Table 1 Test results of alkali loading rate of polymer composite membrane 5. Water absorption test: Use the immersion method, take about 0.3 g of the sample and put it into a beaker filled with 50 mL of pure water, shake it slightly for 5 minutes, soak it for 12 hours, and then record the mass after soaking. Water absorption rate Q = (m1-m0) / m0, where m0 is the mass of the sample before water absorption, and m1 is the mass of the sample after water absorption.

[0042] Table 2 shows the water absorption test results of the polymer composite membrane and Examples 1-2 and Comparative Example 1. It can be seen from the table that compared with Comparative Example 1 and Example 2, the polymer composite membrane and Example 1 have lower water absorption rates, and the water absorption rate of Example 1 is only 1.3% higher than that of the polymer composite membrane, indicating that the water absorption rate of the polymer composite membrane is not greatly affected by the loading of berberine. In addition, although the water absorption rate of Example 2 is higher than that of Example 1, it is still much lower than that of Comparative Example 1. Combined with Table 1, it is further explained that compared with the loading of inorganic bases, the polymer composite membrane prepared by the present invention has a better loading effect on alkaloids while maintaining a lower water absorption rate.

[0043] Table 2 Water absorption test results of polymer composite membranes and Examples 1-2 and Comparative Example 1 6. Hygroscopicity test: A relatively simple method was used to simulate a humid environment. 0.2 g of each sample was placed in a culture dish, and 100 mL of pure water was taken in a beaker. The above items were placed in a closed box, left at room temperature for 24 hours, and then the samples were taken out and weighed. Moisture absorption rate W = (mb-ma) / ma, where ma is the mass of the sample before moisture absorption treatment, and mb is the mass of the sample after moisture absorption treatment.

[0044] Table 3 shows the moisture absorption test results of the polymer composite membrane and Examples 1-2 and Comparative Example 1. It can be seen from the table that the polymer composite membrane has a low moisture absorption rate, and when berberine or matrine is loaded thereon, Examples 1 and 2 still have a low moisture absorption rate. However, the moisture absorption rate of Comparative Example 1 is much greater than that of Examples 1-2 and the polymer composite membrane, and the water absorption is more than 3 times the original mass of the membrane, which is not conducive to the storage of the membrane. Therefore, the alkaloid-loaded polymer composite membrane prepared by the present invention has an extremely low moisture absorption rate, which is conducive to the stable storage of the membrane.

[0045] Table 3 shows the moisture absorption test results of the polymer composite film and Examples 1-2 and Comparative Example 1 7. Organic solvent immersion test: The samples were measured by immersion method. About 0.3 g of each sample was taken and placed in a beaker containing 50 mL of butyl acrylate. After slight shaking for 5 minutes, the samples were immersed for 12 hours. The mass of the samples after immersion was recorded and the mass change was calculated.

[0046] Table 4 is the organic solvent immersion test results of the polymer composite film and the embodiments and comparative examples. It can be seen from the table that after soaking in butyl acrylate, the mass of the composite film, the embodiment and the comparative example all rises to varying degrees, indicating that the composite film prepared by the present invention has a certain lipophilicity, which is conducive to the effective contact of the organic solvent with the polymer composite film, thereby improving the deacidification efficiency. And after loading the alkaloid, the overall lipophilicity of the polymer composite film rises slightly, and from the data of comparative example 2, after loading the inorganic base, the lipophilicity of the polymer composite film decreases, which is not conducive to the contact of the organic solvent. In addition, the loss of the organic solvent is considered. Combined with the deacidification performance test results (Table 6), 0.1g of the film prepared by the present invention can be efficiently deacidified for about 100g of trace acid organic solvent. In this case, the trace loss of the organic solvent can be ignored.

[0047] Table 4 Organic solvent immersion test results of polymer composite membranes and examples and comparative examples 8. Deacidification performance test: Take butyl acrylate as the simulated organic solvent and acetic acid as the simulated acid to test the deacidification performance of the sample. During the test, take 0.1 g, 0.5 g and 1 g of acetic acid, and then take 99.9 g, 99.5 g and 99 g of butyl acrylate respectively. Mix them to make acetic acid-butyl acrylate mixed solutions with acetic acid contents of 0.1%, 0.5% and 1%. Take 0.1 g of each alkali-loaded membrane, put the membrane into the acetic acid-butyl acrylate mixed solution, shake it for 5 minutes, let it stand for 12 hours, and cycle deacidification for 3 times (that is, the same polymer membrane is tested for deacidification with the same acidity 3 times). Determine the concentration of acetic acid in butyl acrylate by high performance liquid chromatography.

[0048] Figure 5 This is the liquid chromatogram of the acetic acid standard sample. It can be seen from the figure that the peak in the time period from 1.67 min to 1.893 min is acetic acid, and the retention time is 1.763 min. Figure 6 : is the liquid chromatogram of the organic solvent after the third deacidification treatment (the liquid chromatograms of the organic solvent after the first and second cyclic deacidification treatments are almost the same as the third one). It can be seen from the figure that almost no peak related to acetic acid can be detected, and it can be seen from Table 6 that after the three deacidification treatments, the acetic acid concentration is less than <1.0 mg / L, indicating that the alkali-loaded polymer membrane prepared by the present invention has a good deacidification effect on acid-containing organic solvents. In addition, it can be seen from Table 4 that the loss of the polymer composite membrane after three cycles is small, indicating that it has a certain stability in the organic solvent and can be recycled.

[0049] Table 5 Changes in the quality of polymer composite membranes Table 6 Deacidification cycle test results The above are only specific embodiments and related tests of the present invention, but the technical features of the present invention are not limited thereto. Any simple changes, equivalent replacements or modifications made based on the present invention to solve basically the same technical problems and achieve basically the same technical effects are all included in the protection scope of the present invention.

Claims

1. Preparation and application of a polymer composite membrane loaded with alkali, characterized in that The preparation method of the alkali-loaded polymer composite membrane comprises the following steps: (1) Preparation of a cross-linking agent: In a beaker, tartaric acid and isocyanoethyl methacrylate were dissolved in tetrahydrofuran to obtain a solution A, and tartaric acid was dissolved in tetrahydrofuran to obtain a solution B. The two solutions were then mixed and stirred at 22-28°C for 22-25h. The tetrahydrofuran was removed by rotary evaporation at 60-70°C to obtain a cross-linking agent. (2) Preparation of polymer composite membrane: Add emulsifier OP-10, sodium dodecyl sulfate (SDS) and deionized water to a 250 ml four-necked flask (equipped with a condensation reflux device, a stirring device, and a constant pressure dropping funnel), stir at 400-600 rpm for 25-35 min, then slowly add butyl acrylate, methyl methacrylate and the crosslinking agent prepared in step (1) using a constant pressure dropping funnel, and continue stirring for 28-35 min. Then transfer the flask to an oil bath, add potassium persulfate solution and polytetrafluoroethylene powder under nitrogen, and polymerize at 78-85°C for 5.5-6.5 h. After the reaction is completed and cooled to 22-28°C, add ammonia water to adjust the pH to 7. Then the mixed solution was transferred to a beaker and a certain amount of ethanol was added, and after being placed in a ventilated place for 24 to 28 hours, the mixed solution was transferred to a polytetrafluoroethylene plate and dried in an oven at 58 to 65°C for 24 to 28 hours to obtain a polymer composite membrane; (3) Preparation of alkali-loaded polymer composite membrane: The polymer composite membrane prepared in step (2) is completely immersed in a saturated solution of alkaloids and allowed to stand for 22 to 26 hours, and then dried at 100 to 110° C. for 22 to 36 hours to finally obtain an alkali-loaded polymer composite membrane.

2. The alkali-loaded polymer composite membrane according to claim 1, characterized in that In step (1), the mass ratio of tartaric acid, isocyanoethyl methacrylate and tetrahydrofuran in solution A is 1:(2-3):(9-11), and the mass ratio of tartaric acid and tetrahydrofuran in solution B is 1:(10-15).

3. The alkali-loaded polymer composite membrane according to claim 1, characterized in that: In step (2), the ratio of the mass (g) of sodium dodecyl sulfate (SDS), the mass (g) of emulsifier OP-10 and the volume (mL) of deionized water is 1: (1.5-1.8): (550-600).

4. The alkali-loaded polymer composite membrane according to claim 1, characterized in that: In step (2), the mass ratio of butyl acrylate, methyl methacrylate and the cross-linking agent mixed solution prepared in step (1) is 1: (0.8-1.2): (0.5-1).

5. The alkali-loaded polymer composite membrane according to claim 1, characterized in that: In step (2), the mass ratio of sodium dodecyl sulfate (SDS) to butyl acrylate is 1: (30-35), and the mass ratio of butyl acrylate to polytetrafluoroethylene powder is 1: (4.2-4.5).

6. The alkali-loaded polymer composite membrane according to claim 1, characterized in that: In step (2), the ratio of the mass (g) of butyl acrylate to the volume (mL) of the potassium persulfate solution is 1:(1.5-1.8), wherein the concentration of the potassium persulfate solution is 10 g / L.

7. The alkali-loaded polymer composite membrane according to claim 1, characterized in that: In step (2), the volume ratio of ethanol to the original mixed solution in the beaker is 1:(0.5-0.8).

8. The alkali-loaded polymer composite membrane according to claim 1, characterized in that: In step (3), the alkaloid is berberine or matrine.

9. Use of a base-loaded polymer composite membrane prepared by the method according to claims 1 to 8 in deacidification of organic solvents.